2019
DOI: 10.1111/saje.12226
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Works Programme on Child Labour in Ethiopia

Abstract: Given the conventional wisdom that poverty and associated income shocks are the fundamental causes of child labour, from a policy perspective, there is a perception that social safety net programmes can play a vital role in reducing child labour. While there is extensive evidence that shows the prevalence of child labour is low among beneficiaries of conditional cash transfer programmes, the impact of workfare programs on child labour has been rarely investigated in the economics literature. This paper address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…Gender variation among children in the household are also an important factor for heterogeneity in child labour outcomes. Among eleven (n = 11) studies included in the current review which reported reduction in child participation in labour, four studies reported that in-kind and cash transfers reduced participation for boys [46,50,51] than for girls, and one study reported reduced participation of both boys and girls in labour due to transfer programs [45]. The remaining eight (n = 8) studies did not report genderrelated variation on effects of social transfer programs on child labour.…”
Section: Child Gendermentioning
confidence: 94%
See 3 more Smart Citations
“…Gender variation among children in the household are also an important factor for heterogeneity in child labour outcomes. Among eleven (n = 11) studies included in the current review which reported reduction in child participation in labour, four studies reported that in-kind and cash transfers reduced participation for boys [46,50,51] than for girls, and one study reported reduced participation of both boys and girls in labour due to transfer programs [45]. The remaining eight (n = 8) studies did not report genderrelated variation on effects of social transfer programs on child labour.…”
Section: Child Gendermentioning
confidence: 94%
“…Finally, with regards to paid work outside the household, among 27 studies included in the review, twelve (n = 12; 44.4%) studies [33,37,38,43,[48][49][50][51][52][53][54][55] reported a decline in decline in children's involvement in paid work outside the household; from these, five studies [38,48,51,52,54] reported significant results. Additionally, one study reported significant decline in children's involvement in paid domestic work outside the household is reduced by 7.7% [36](p < 0.000).…”
Section: Program Type and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, innovative dimensions of PWPs have emerged with the sole aim of achieving extra goals. Add-on interventions, such as capital infusion, training and mentoring, and behavioral therapy components are being inculcated into PWPs to improve the quality of labor supply and develop programs into more or less permanent initiatives so as to attain social protection goals, e.g., restoring dignity, reducing child labor and gender inequality (Dejardin, 1996;Holmes and Jones, 2011;Rimki, 2012;Ehmke, 2015;Kumar, 2017;Gehrke and Hartwig, 2018;Dinku, 2019;Mission Directorate, 2021) and maintaining social and political stability, particularly in fragile states (Mvukiyehe, 2018). This new image given to PWPs leaves only a thin commonality between all PWPs−they are all poised to (1) minimize persistent poverty through provision of low-wage employment opportunities for the vulnerable poor and at-risk youths, and (2) create or upgrade (repair) community assets e.g., social and economic infrastructure (The World Bank, 2009;Mvukiyehe, 2018).…”
Section: Introductionmentioning
confidence: 99%